When high self-efficacy backfires: Understanding withholding effort among healthcare workers during communicable diseases outbreaks - Popoola, Olusola S. (International Journal of Innovative Research and Scientific Studies, 2025)
Healthcare workers (HCWs) are often at the frontline of communicable disease outbreaks, facing heightened risks that can influence their propensity to withhold effort. This study examined the influence of socio-cognitive factors (risk perception, perceived vulnerability to disease, and self-efficacy) on withholding effort among HCWs during communicalbe disease outbreaks. Using a quantitative cross-sectional survey with a high response rate (87%), data were collected from 477 HCWs across selected hospitals in Ondo State, Nigeria. A 2×2×2 factorial design was employed to test the hypotheses. Results showed that higher risk perception [F (1, 469)=13.89, P<.001, η²=.029], higher perceived vulnerability to disease [F (1, 469)=22.95, P<.001, η²=.047], and higher self-efficacy [F (1, 469)=10.04, P<.05, η²=.021] were associated with increased withholding effort. The interaction between self-efficacy and perceived vulnerability was significant [F (1, 469)=10.10, P<.05, η²=.021], indicating that the positive effect of self-efficacy on withholding effort emerged most strongly when vulnerability to disease was high (M=29.01). These findings highlight that withholding effort is not always a failure of motivation but reflects a protective response to perceived threats. The study recommends targeted and structured training to build confidence, a supportive work environment, and adequate resources to reduce withholding effort and sustain healthcare workers’ commitment during future outbreaks.